Frequency of Symptoms and Signs of Primary Vascular Dysregulation in Swiss and Korean Populations - Konieczka, K.; Choi, H. J.; Koch, S.; Schoetzau, A.; Küenzi, D.; Kim, D. M. (Klinische Monatsblätter für Augenheilkunde, 2014)
Background: Primary vascular dysregulation syndrome (also called Flammer syndrome) is related to certain eye diseases, particularly normal tension glaucoma. Primary vascular dysregulation is characterized by a number of symptoms and signs (e.g., cold hands and/or feet, low blood pressure), that occur more frequently in subjects with primary vascular dysregulation compared to the general population. The aim of the present study was to test and compare the relative frequency of symptoms and signs related to primary vascular dysregulation in unselected populations in Switzerland and Korea.Subjects and Methods: Swiss (n = 259) and Korean (n = 1116) subjects filled out our questionnaire containing 15 questions related to symptoms and signs of primary vascular dysregulation.Results: In the populations studied, seven of 15 symptoms and signs of primary vascular dysregulation (increased smell perception, increased pain sensation, increased response to certain drugs, low body mass index, feeling cold, cold hands and/or feet, and headaches) occurred significantly more often in the Swiss population than in the Korean population, whereas five symptoms and signs (reversible skin blotches, tendency toward perfectionism, long sleep onset time, tinnitus, and dizziness) occurred significantly more often in the Korean population.Conclusion: The relative frequency of these symptoms and signs of primary vascular dysregulation in an unselected average population differs between Switzerland and Korea. Therefore, if a diagnosis of primary vascular dysregulation is based on the self-reported symptoms and signs of the patient, they must be compared with the frequency of symptoms and signs in the corresponding local population.
Keywords: ocular blood flow; primary vascular dysregulation syndrome (Flammer syndrome); vasospasm; frequency of symptoms and signs; general population